The Narrative Review of Published Evidence on Cost Analysis and Sustainability of the Virtual Fracture Clinic Model: A Report Based Study - Gitana Diana Stukaite (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Background: Currently, there is paucity of published evidence on the Virtual Fracture Clinic (VFC) model. There are limited resources from which conclusions could be drawn relating to the management of orthopaedic conditions, cost effectiveness, quality and safety, patient satisfaction rates and management when using the VFC model. Objectives: This narrative review of current published evidence aims to reveal how cost effective the VFC model is in relation to the orthopaedic management of both children and adults in the United Kingdom (UK). The review also seeks to identify gaps in current available literature and make recommendations for further research into the VFC model. Methods: This narrative review is secondary research of the evidence available on the VFC using a systematic approach. Seven electronic databases were searched to identify relevant peer-reviewed studies published since January 2010. The literature review identified 678 initial articles produced by undertaking key word searches (see appendix II). A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram was used to assist in illustrating the process of filtering and applying the inclusion and exclusion criteria to the search retrieval which subsequently led to 32 articles [1]. In total 14 relevant papers were selected following deduplication. Seven studies of various study types were selected and subjected to critical analysis using a systematic approach [2]. The main themes that have been selected are identified in Table 2. Results: No Randomised Controlled Trials (RCTs) or systematic reviews were found regarding VFCs. Seven articles were identified and reviewed following an in-depth databases search, these consisted of clinical audits, simulation study, comparison study, perspective analysis and retrospective research. All studies were from the UK only. One paper focused on paediatric fractures, two dedicated their research to Webber B ankle breaks and fifth metatarsal, including Jones fractures. The other four research articles consisted of mainly cost comparison and service redesign studies. All studies but one, by White et al. [3] reported positive findings. Overall, cost effectiveness of VFCs ranged from £13.91 per patient to £122. Individual study trusts estimated variable cost savings, ranging from £81,920 to £212,705, also Nationally approximate projections confirmed sums reaching £1,1 million per year. Conclusion: This narrative review shows that there are potential cost savings to be made when using the VFC model. Current financial projections cannot be taken for granted at this present time. Further robust evidence such as RCTs or systematic reviews with meta-analysis are required before final conclusions can be drawn regarding cost effectiveness when using the VFC model throughout the UK.